IMPROVING OF SOCIETY'S KNOWLEDGE ABOUT PREVENTION OF CORONARY HEART DISEASE FROM AN EARLY AGE - Meli Diana; Dini Prastyo Wijayanti; Dimas Hadi Prayoga; Nurhanifah Mawarni; Kiki Widyasari (Institute for Research and Community Service, Health Polytechnic of Kerta Cendekia, Sidoarjo, 2021)
Community Service activities organized by Health Polytechnic of Kerta Cendekia, Sidoarjo in collaboration with Baitul Mal Hidayatulloh (BMH) Sidoarjo held a Health Talk Show which was broadcast live streaming on the POS DAI SIDOARJO channel with the theme